Slow Innovation: the need for reflexivity in Responsible Innovation (RI). Issue 2 (4th May 2021) - Steen, Marc
ABSTRACT: In this essay, the author reflects on several personal experiences in projects and advocates Slow Innovation as an alternative to the putative need for speed, the primacy of efficiency and the assumption that faster is better. Yes, RI does take time. Let us wear Slow Innovation as a badge of honour. Let us promote reflexivity : make time for uneasy questions, vulnerable experiences, awkward moments and uncertainty. The essay closes with an example of how this may support a human-centric approach to Artificial Intelligence.